Perbandingan Pengujian Aktivitas Antibakteri Starter Yogurt dengan Metode Difusi Sumuran dan Metode Difusi Cakram - Lilih Siti Nurhayati; Nadhira Yahdiyani; Akhmad Hidayatulloh (Unpad Press, 2020)
Antibacterial activity testing can be done using the agar diffusion method, including agar well diffusion and disk diffusion agar methods. This study aims to compare two antibacterial testing methods to analyze the anti-bacterial activity of a yogurt starter against the bacteria Escherichia coli and Staphylococcus aureus. The study was conducted experimentally with 5 concentrations of yogurt starter, namely 2%, 4%, 6%, 8%, and 10%. Testing antibacterial activity using two methods, disk diffusion agar and well diffusion agar methods. The research showed that agar well diffusion method obtained antibacterial activity greater than the disk diffusion method for E. coli and S. aureus.